Inorganic fiber composite aerogel board and its application

Through the layering method and molding process of inorganic fiber composite airgel panels, the problem of limited performance improvement of steel plates in terms of fire resistance, anti-corrosion, and weather resistance is solved, and the efficient heat insulation, flame retardancy, and corrosion resistance of steel plates are improved. Applicable to multiple technical fields.

CN118306068BActive Publication Date: 2025-01-21POLY CHANGDA ENGINEERING CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410501944.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2025-01-21
Estimated Expiration
2044-04-25

AI Technical Summary

Technical Problem

The performance improvement of existing steel plates in terms of fire resistance, corrosion resistance, weather resistance, etc. is limited, and the existing fire resistance protection measures are costly and have poor results, and are highly limited, making it difficult to adapt to sensitive environments such as humidity, high temperature, strong acid or strong alkali.

Method used

Inorganic fiber composite airgel panels are used to prepare composite materials with high-temperature-resistant flame-retardant sealants through a process that combines lamination and molding methods, including fire-resistant, waterproof and corrosion-resistant layers, thermal insulation layers and original steel plate layers. , improve the heat insulation, flame retardant, waterproof and corrosion resistance properties of steel plates.

Benefits of technology

It realizes that the steel plate can maintain high strength while improving the thermal insulation performance, flame retardant performance and corrosion resistance. The flame retardant performance is efficient and stable, which can effectively inhibit the spread of flames, reduce heat conduction, and enhance the competitiveness of the steel plate. The process is simple and low-cost. Low, suitable for construction, automobile, aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118306068B_ABST
    Figure CN118306068B_ABST
Patent Text Reader

Abstract

The present invention discloses an inorganic fiber composite aerogel board and its application, which belongs to the technical field of new environmentally friendly fire-resistant materials. A steel plate is selected as the inner panel, and the ceramic silicone rubber fiber belt and the aerogel felt are cut into the same size; the steel plate, high temperature resistant flame retardant sealant, aerogel felt, high temperature resistant flame retardant sealant, and ceramic silicone rubber fiber belt are laid and bonded neatly in sequence by layer laying method, molded, and the high temperature resistant flame retardant sealant is applied on the side of the aerogel board for structural edge sealing, and then left to solidify. The present invention greatly reduces the undesirable phenomena such as hardness drop, softening, and deformation of the steel plate under high temperature; the molding can make the various layers of the structure fully bonded to form an integrated composite plate, ensuring the stable performance of the material, and not prone to local damage or falling off during use; the aerogel board of the present invention has a simple preparation process, low thermal conductivity, high peel strength between the layers, and excellent mechanical properties, fire resistance, heat insulation, and thermal insulation performance, waterproof and corrosion-resistant sealing performance, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of novel environmentally friendly fire-resistant materials, and in particular, relates to an inorganic fiber composite aerogel board and application thereof. Background Art

[0002] In recent years, steel plates have been widely used in construction, bridges, ships, vehicles, boilers, high-pressure vessels, oil and gas pipelines and other industries due to their high strength, light weight, good overall stiffness and deformation resistance. However, the poor fire resistance, corrosion resistance, weather resistance and plasticity of steel plates limit their application range. Under normal circumstances, the fire resistance limit of steel plates is within the range of 15 to 20 minutes. The fire protection measures taken for steel plates mainly include cast-in-place method, coating method, encapsulation method, spraying method, etc. Under normal circumstances, the protection thickness of the above methods needs to reach 4 to 5 cm to make the overall structure meet the requirements of the first and second level fire resistance grades. The existing methods are not only expensive, ineffective and have great limitations. In addition, steel plates should also adapt to sensitive environmental factors during use, such as humid climate, high temperature, strong acid or strong alkali, otherwise it will cause corrosion of the steel plate and reduce the service life, resulting in the risk of structural shedding and collapse, causing unnecessary loss of life and property. The existing technology has limited improvement in fire resistance, corrosion resistance and weather resistance of steel plates, and the cost is relatively high.

[0003] The present invention provides an inorganic fiber composite aerogel board and its application. The board can be mainly divided into three layers, including a fire-resistant, waterproof and corrosion-resistant layer, a thermal insulation layer and an original steel plate layer. The board has a simple preparation process, low thermal conductivity, high peel strength between layers, and excellent mechanical properties, fire-resistant, thermal insulation, waterproof, corrosion-resistant and sealing properties. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide an inorganic fiber composite aerogel plate and application thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] An inorganic fiber composite aerogel plate is prepared by the following steps:

[0007] (1) A steel plate is selected as the inner panel, and the ceramicized silicone rubber fiber belt and aerogel felt are cut into the same size;

[0008] (2) Using the layer laying method, the steel plate, the high temperature resistant flame retardant sealant, the aerogel felt, the high temperature resistant flame retardant sealant, and the ceramicized silicone rubber fiber tape are laid and bonded neatly in sequence;

[0009] (3) After the laying is completed, it is molded using molding equipment;

[0010] (4) After the molding is completed, a high temperature resistant flame retardant sealant is applied to the side of the fiber composite aerogel board for structural edge sealing. After completion, the inorganic fiber composite aerogel board can be obtained by standing and curing.

[0011] The materials selected for the inorganic fiber composite aerogel board are all low thermal conductivity, high temperature resistance, aging resistance, corrosion resistance, green, lightweight, and environmentally friendly materials; the inorganic fiber composite aerogel board manufacturing process is a combination of layer laying method and molding method. The board is not easy to deform during molding and has good dimensional stability. It can press large flat boards, and the equipment is simple, the effect is high, the construction progress is fast, and the cost is low; after the molding is completed, the edge is sealed with a high temperature resistant flame retardant sealant, which on the one hand ensures the fire resistance and heat insulation performance of the outer surface of the inorganic fiber composite aerogel board, and on the other hand, improves the overall sealing of the board. The inorganic fiber composite aerogel board of the present invention is a new type of composite material with the characteristics of light weight, high strength, heat insulation, and flame retardancy.

[0012] Furthermore, the ceramic silicone rubber fiber belt in step (1) is a composite of one of glass fiber cloth, basalt fiber cloth, and carbon fiber cloth and ceramic silicone rubber.

[0013] Furthermore, the aerogel felt in step (1) is one of glass fiber aerogel felt, basalt fiber aerogel felt, and high silica fiber aerogel felt.

[0014] Furthermore, the thickness of the steel plate in step (1) is 1 to 3 mm.

[0015] Furthermore, the thickness of the ceramicized silicone rubber fiber belt in step (1) is 1 mm.

[0016] Furthermore, the aerogel felt in step (1) has a thickness of 3 to 6 mm.

[0017] Furthermore, the thickness of the high temperature resistant flame retardant sealant in step (2) is 0.5 to 1 mm.

[0018] Furthermore, in step (3), the molding pressure is 3-5 MPa, and the molding holding time is 3 min.

[0019] Furthermore, the thickness of the high temperature resistant flame retardant sealant in step (4) is 1 mm.

[0020] Furthermore, the high temperature resistant flame retardant sealant comprises 40-50 parts of terminal hydroxyl polysiloxane, 5-10 parts of cross-linking agent, 10-15 parts of flame retardant, 10-20 parts of nano calcium carbonate, 0.5-2 parts of chain extender, and 0.5-1 part of stannous octoate.

[0021] Furthermore, the crosslinking agent is one or more of methyltriacetoxysilane, methyltributylidene oxime silane, and methyltrimethoxysilane.

[0022] Furthermore, the flame retardant is prepared by the following steps:

[0023] S1. In a three-necked flask at room temperature and under nitrogen protection, 4-aminophenylboronic acid, caged pentaerythritol phosphate and dimethyl sulfoxide were added in sequence, stirred to dissolve, and then concentrated hydrochloric acid was slowly added. The reaction was stirred for 2 h at room temperature. After the reaction was completed, sodium carbonate was added for neutralization, and most of the solvent was removed by vacuum distillation. Finally, the product was washed with deionized water for 5 times and with anhydrous ethanol for 5 times. After washing, the product was vacuum dried at 80° C. for 12 h to obtain intermediate 1; the dosage ratio of 4-aminophenylboronic acid, caged pentaerythritol phosphate, concentrated hydrochloric acid and dimethyl sulfoxide was 7.6 g:8.6 g:0.025 mL:130 mL;

[0024] The molar ratio of 4-aminophenylboronic acid to diethyl hydroxymethylphosphonate is controlled to be 1:1 and 4-aminophenylboronic acid is slightly excessive. A boron hydroxyl group of 4-aminophenylboronic acid can react with a hydroxyl group of caged pentaerythritol phosphate under the catalysis of concentrated hydrochloric acid to undergo esterification reaction. The reaction process is as follows:

[0025]

[0026] S2. First, a dry brown three-necked flask was purged with nitrogen for 30 minutes, and then intermediate 1, 1-piperazine propanol and dimethyl sulfoxide were added, and the mixture was stirred until dissolved. Then, concentrated hydrochloric acid was slowly added, and the reaction was stirred at room temperature for 3 hours. After the reaction was completed, sodium carbonate was added for neutralization, and then the mixture was distilled under reduced pressure. The crude product was washed with deionized water 5 times, with anhydrous ethanol 5 times, and finally dried under vacuum at 80°C for 12 hours to obtain intermediate 2; the amount ratio of intermediate 1, 1-piperazine propanol, concentrated hydrochloric acid and dimethyl sulfoxide was 10.5g:5.8g:0.02mL:130mL;

[0027] The molar ratio of intermediate 1 to 1-piperazinyl propanol is controlled to be 1:1 and 1-piperazinyl propanol is slightly excessive. A boron hydroxyl group of intermediate 1 can react with a hydroxyl group of 1-piperazinyl propanol under the promotion of an acid catalyst to undergo an esterification reaction. The reaction process is as follows:

[0028]

[0029] S3, after the intermediate 2 and DMF (N, N-dimethylformamide) are mixed and dissolved evenly, a reaction solution is obtained and set aside; first, the dry three-necked flask is blown with nitrogen for 30 minutes, then KH570 (3-(methacryloyloxy)propyltrimethoxysilane) is added, and then the reaction solution is slowly dripped into the three-necked flask with a constant pressure dropping funnel, and the reaction is carried out at 60°C for 48 hours. After the reaction is completed, it is cooled to room temperature and distilled under reduced pressure. The whole process is carried out under nitrogen protection to obtain a flame retardant. The amount ratio of intermediate 2, KH570 and DMF is 9.4g:5.5mL:100mL.

[0030] Intermediate 2 undergoes Michael addition reaction with KH570, and the reaction process is as follows:

[0031]

[0032] Flame retardants containing P elements promote the carbonization of the polymer matrix and form a molten carbon layer on the surface of the polymer matrix; flame retardants containing N elements decompose under heat to generate non-combustible gases such as ammonia and nitrogen, which not only dilute the concentration of combustible gases in the flame zone, but also make the molten carbon layer formed on the surface of the polymer matrix expand and foam to form a porous foam structure. The expanded porous foam carbon layer will block the process of heat and oxygen exchange between the material and the outside world, preventing it from burning; flame retardants containing B elements mainly play a flame retardant role in the condensed phase, and can promote carbonization by changing the decomposition mode and dehydration of the polymer; the presence of Si elements strengthens the carbon layer on the surface of the matrix, blocks the flame, and further enhances the flame retardant effect; therefore, the four elements B, N, P, and Si in the flame retardant synergistically flame retardant, giving the sealant excellent flame retardant properties.

[0033] The flame retardant contains siloxane bonds, which are hydrolyzed to form Si-OH bonds. Adjacent Si-OH bonds are dehydrated and cross-linked. At the same time, the Si-OH bonds condense with the hydroxyl groups on the surface of nano-calcium carbonate and the hydroxyl groups of terminal hydroxyl polysiloxane to form covalent bonds, which not only disperse the nano-calcium carbonate and terminal hydroxyl polysiloxane, but also disperse the flame retardant. The flame retardant is combined with raw materials such as nano-calcium carbonate and terminal hydroxyl polysiloxane through chemical reactions. Therefore, the flame retardant is not easily affected by time and the external environment and migrates or comes out. Therefore, the flame retardant of the sealant is stable and excellent, and the inorganic fiber composite aerogel board has a long-lasting, efficient and safe flame retardant effect.

[0034] Furthermore, the chain extender is one or more of dimethyl dibutyl ketone oxime silane, methyl vinyl dibutyl ketone oxime silane or methyl vinyl diacetone oxime silane.

[0035] The invention also discloses the application of an inorganic fiber composite aerogel board in the fields of construction, automobile and aerospace.

[0036] Beneficial effects of the present invention:

[0037] (1) The present invention uses a high temperature resistant flame retardant sealant to bond and mold the original steel plate with the fireproof, waterproof and corrosion resistant layer and the thermal insulation layer, so that the steel plate has improved thermal insulation, flame retardant and corrosion resistance while maintaining a high strength, and the flame retardant performance is efficient and stable, which can greatly reduce the conduction of heat and effectively inhibit the spread of flames, and improve the competitiveness of the steel plate in the fields of thermal insulation, fire resistance, etc. In addition, considering the use requirements, the fiber composite aerogel plate is only 5 to 10 mm thicker than the steel plate, and the weight is negligible.

[0038] (2) The present invention selects a combination of layer laying and molding in the manufacturing process. Compared with common composite material manufacturing processes such as vacuum blistering, automatic weaving, bonding, and injection molding, which have complex equipment, high equipment cost, shape restrictions, fiber direction restrictions and dispersion, and insufficient durability, the layer laying process can select different fiber directions and numbers of layers as needed and is suitable for various fibers to meet the needs of different applications. The molding process can form an organic whole between the layers through a high-temperature resistant flame-retardant sealant, so that the high-temperature resistant flame-retardant sealant can be bonded under a certain pressure and penetrate into the aerogel felt structure. After the high-temperature resistant flame-retardant sealant is cured, the uniformity and integrity of the composite material are ensured and the density and strength of the composite material are improved. Not only that, the molding process is usually suitable for mass production and can quickly prepare a large number of composite products.

[0039] (3) The main structure of the present invention is ceramicized silicone rubber fiber belt + aerogel felt + original specimen steel plate, which are bonded with high temperature resistant flame retardant sealant. At the same time, natural basalt fiber is used as the base material, which does not contain harmful substances and has a lower environmental impact. In contrast, other fire resistant and anti-corrosion measures for steel plates always involve a large amount of energy consumption and environmental pollution during the construction process. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The present invention will be further described below in conjunction with the accompanying drawings.

[0041] Figure 1 The present invention is a process flow chart of manufacturing an inorganic fiber composite aerogel board;

[0042] Figure 2 This is a cross-sectional structural diagram of an inorganic fiber composite aerogel board;

[0043] The following are the descriptions of the reference numerals:

[0044] 1. Steel plate layer; 2. Aerogel felt layer; 3. Ceramic silicone rubber fiber belt layer. DETAILED DESCRIPTION

[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] The flame retardant is prepared in the following specific steps:

[0048] S1. In a 250 mL three-necked flask, 7.6 g of 4-aminophenylboronic acid, 8.6 g of caged pentaerythritol phosphate and 130 mL of dimethyl sulfoxide were added in sequence at room temperature and under nitrogen protection. The mixture was stirred to dissolve. Subsequently, 0.025 mL of concentrated hydrochloric acid was slowly added. The mixture was stirred at room temperature for 2 h. After the reaction was completed, sodium carbonate was added for neutralization. Most of the solvent was removed by vacuum distillation. The mixture was washed with deionized water for 5 times and with anhydrous ethanol for 5 times. After washing, the product was dried under vacuum at 80 °C for 12 h to obtain intermediate 1.

[0049] S2. First, a dry 250mL brown three-necked flask was purged with nitrogen for 30min, and then 10.5g of intermediate 1, 5.8g of 1-piperazine propanol and 130mL of dimethyl sulfoxide were added, and the mixture was stirred until dissolved. Then, 0.02mL of concentrated hydrochloric acid was slowly added, and the mixture was stirred and reacted at room temperature for 3h. After the reaction, sodium carbonate was added for neutralization, and then the mixture was distilled under reduced pressure. The crude product was washed with deionized water 5 times, with anhydrous ethanol 5 times, and finally dried under vacuum at 80°C for 12h to obtain intermediate 2.

[0050] S3. Mix and dissolve 9.4 g of intermediate 2 and 100 mL of DMF evenly to obtain a reaction solution for use; first, blow nitrogen gas into a dry 250 mL three-necked flask for 30 min, then add 5.5 mL of KH570, and then slowly drip the reaction solution into the three-necked flask using a constant pressure dropping funnel, react at 60°C for 48 h, cool to room temperature after the reaction is completed, and distill under reduced pressure. The whole process is carried out under nitrogen protection to obtain a flame retardant.

[0051] Example 2

[0052] The specific steps for preparing high temperature resistant flame retardant sealant are as follows:

[0053] 40 parts of terminal hydroxyl polysiloxane and 10 parts of nano calcium carbonate were stirred and mixed at room temperature, heated to 130°C and stirred in vacuum for 2 hours to remove moisture from the system, then cooled to room temperature, ground evenly, discharged, vacuumed and stirred to remove moisture from the air, and then 10 parts of the flame retardant of Example 1 and 5 parts of methyltriacetoxysilane were added and mixed evenly, followed by adding 0.5 parts of dimethyl dibutyl ketoxime silane and 0.5 parts of stannous octoate, mixing evenly, and removing bubbles to obtain a high temperature resistant flame retardant sealant.

[0054] Example 3

[0055] The specific steps for preparing high temperature resistant flame retardant sealant are as follows:

[0056] 48 parts of terminal hydroxyl polysiloxane and 15 parts of nano calcium carbonate were stirred and mixed at room temperature, heated to 140°C and stirred in vacuum for 3 hours to remove moisture from the system, then cooled to room temperature, ground evenly, discharged, vacuumed and stirred to remove moisture from the air, and then 13 parts of the flame retardant of Example 1 and 8 parts of vinyl trisbutyl ketoxime silane were added and mixed evenly, followed by adding 1.5 parts of methyl vinyl dibutyl ketoxime silane and 0.8 parts of stannous octoate, mixed evenly, and then bubbles were removed to obtain a high temperature resistant flame retardant sealant.

[0057] Example 4

[0058] The specific steps for preparing high temperature resistant flame retardant sealant are as follows:

[0059] 50 parts of terminal hydroxyl polysiloxane and 20 parts of nano calcium carbonate were stirred and mixed at room temperature, heated to 150°C and stirred in vacuum for 4 hours to remove moisture from the system, then cooled to room temperature, ground evenly, discharged, vacuum stirred to remove moisture from the air, and then 15 parts of the flame retardant of Example 1 and 10 parts of methyltrimethoxysilane were added and mixed evenly, followed by adding 2 parts of methyl vinyl diacetone oxime silane and 1 part of stannous octoate, mixed evenly, and then bubbles were removed to obtain a high temperature resistant flame retardant sealant.

[0060] Example 5

[0061] Figure 1 It is a process flow chart of manufacturing an inorganic fiber composite aerogel board;

[0062] Reference Figure 1 The process for preparing the inorganic fiber composite aerogel board is as follows:

[0063] (1) A 3 mm steel plate was selected as the inner panel, and a 1 mm ceramic silicone rubber fiber tape and a 3 mm glass fiber aerogel felt formed by a composite of glass fiber cloth and ceramic silicone rubber were cut into the same size;

[0064] (2) using a layer-laying method, the steel plate of step 1, the high temperature resistant flame retardant sealant of embodiment 2, the aerogel felt of step 1, the high temperature resistant flame retardant sealant of embodiment 2, and the ceramic silicone rubber fiber tape of step 1 are laid and bonded neatly in sequence; the thickness of the high temperature resistant flame retardant sealant is 0.5 mm;

[0065] (3) After the laying is completed, the molding equipment is used for molding, the pressure is 3Mpa, and the pressure is maintained for 3 minutes, so that the structural plate is formed;

[0066] (4) After the molding is completed, a 1 mm thick high temperature resistant flame retardant sealant of Example 2 is applied to the side of the fiber composite aerogel board for structural edge sealing. After completion, the inorganic fiber composite aerogel board is obtained by standing and curing.

[0067] Example 6

[0068] Reference Figure 1 The process for preparing the inorganic fiber composite aerogel board is as follows:

[0069] (1) A 2 mm steel plate was selected as the inner panel, and a 1 mm ceramic silicone rubber fiber belt and a 5 mm high silica fiber aerogel felt formed by a composite of carbon fiber cloth and ceramic silicone rubber were cut into the same size;

[0070] (2) using a layer-laying method, the steel plate of step 1, the high temperature resistant flame retardant sealant of embodiment 3, the aerogel felt of step 1, the high temperature resistant flame retardant sealant of embodiment 3, and the ceramic silicone rubber fiber tape of step 1 are laid and bonded neatly in sequence; the thickness of the high temperature resistant flame retardant sealant is 0.8 mm;

[0071] (3) After the laying is completed, the molding equipment is used for molding, the pressure is 4Mpa, and the pressure is maintained for 3 minutes, so that the structural plate is formed;

[0072] (4) After the molding is completed, a 1 mm thick high temperature resistant flame retardant sealant of Example 3 is applied to the side of the fiber composite aerogel board for structural edge sealing. After completion, the inorganic fiber composite aerogel board is obtained by standing and curing.

[0073] Example 7

[0074] Reference Figure 1 The process for preparing the inorganic fiber composite aerogel board is as follows:

[0075] (1) A 1 mm steel plate was selected as the inner panel, and a 1 mm ceramic silicone rubber fiber belt and a 6 mm basalt fiber aerogel felt formed by a composite of basalt fiber cloth and ceramic silicone rubber were cut into the same size;

[0076] (2) using a layer-laying method, the steel plate of step 1, the high temperature resistant flame retardant sealant of embodiment 4, the aerogel felt of step 1, the high temperature resistant flame retardant sealant of embodiment 4, and the ceramicized silicone rubber fiber tape of step 1 are laid and bonded neatly in sequence; the thickness of the high temperature resistant flame retardant sealant is 1 mm;

[0077] (3) After the laying is completed, the molding equipment is used for molding, the pressure is 5Mpa, and the pressure is maintained for 3 minutes, so that the structural plate is formed;

[0078] (4) After the molding is completed, a 1 mm thick high temperature resistant flame retardant sealant of Example 4 is applied to the side of the fiber composite aerogel board for structural edge sealing. After completion, the inorganic fiber composite aerogel board is obtained by standing and curing.

[0079] Figure 2 FIG. 1 is a cross-sectional view of the inorganic fiber composite aerogel plate prepared in this embodiment. Figure 2 As shown, it includes a steel plate layer 1, an aerogel felt layer 2 and a ceramic silicone rubber fiber belt layer 3 arranged in sequence, wherein the aerogel felt layer 2 is used as a thermal insulation layer; the ceramic silicone rubber fiber belt layer 3 is used as a fireproof, waterproof and anti-corrosion layer. In order to ensure the fireproof and heat-insulating properties, corrosion resistance and air tightness of the overall structure of the board, a 1mm thick high-temperature resistant flame-retardant sealant is used for structural edge sealing after the molding process.

[0080] Comparative Example 1

[0081] The specific steps for preparing high temperature resistant flame retardant sealant are as follows:

[0082] The remaining steps remain unchanged, only the flame retardant in Example 4 is replaced by ammonium polyphosphate to prepare a high temperature resistant flame retardant sealant.

[0083] Comparative Example 2

[0084] The inorganic fiber composite aerogel board is prepared in the following specific steps:

[0085] The remaining steps remain unchanged, only the high temperature resistant flame retardant sealant of Example 7 is replaced by the high temperature resistant flame retardant sealant of Comparative Example 1 to prepare an inorganic fiber composite aerogel board.

[0086] Performance Testing

[0087] The high temperature resistant flame retardant sealants prepared in Examples 2-4 and Comparative Example 1 were prepared into dumbbell-shaped specimens according to the provisions of GB / T2941, and the tensile strength and elongation at break were tested with reference to GB / TT528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", with a tensile speed of 500 mm / min; the oxygen index of the high temperature resistant flame retardant sealants prepared in Examples 2-4 and Comparative Example 1 was tested with reference to GB / TT2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test"; the vertical burning grade of the high temperature resistant flame retardant sealants prepared in Examples 2-4 and Comparative Example 1 was tested with reference to UL94-2009 standard; the test results are shown in Table 1:

[0088] Table 1

[0089]

[0090] It can be seen from Table 1 above that the high temperature resistant flame retardant sealant according to the embodiment of the present invention has excellent flame retardant properties.

[0091] The thermal conductivity of the inorganic fiber composite aerogel plates of Examples 5-7 and Comparative Example 2 was tested with reference to GB / T10295-2008; three parallel samples of the inorganic fiber composite aerogel plates of Examples 5-7 and Comparative Example 2 were respectively taken and immersed in deionized water at room temperature, and the inorganic fiber composite aerogel plates were dried at 110°C for 1 hour, and the dry weight M1 was measured, and the wet weight M2 was measured after wiping with a dry cloth after soaking for 24 hours. The water absorption rate was calculated according to the water absorption rate = (M2-M1) / M1×1000; the test results are shown in Table 2:

[0092] Table 2

[0093] project Thermal conductivity is lower than W / m﹒k Water absorption rate‰ Example 5 0.04 1.2 Example 6 0.04 1.1 Example 7 0.04 1.0 Comparative Example 2 0.04 2.5

[0094] It can be seen from the results in Table 2 that the inorganic fiber composite aerogel plates prepared in Examples 5-7 of the present invention have better waterproof properties, and the inorganic fiber composite aerogel plates in Examples 5-7 have low thermal conductivity and good thermal insulation effect.

[0095] The present invention ensures the high strength, light weight, good overall rigidity and deformation resistance of the steel plate while strengthening its waterproof, fire-resistant, heat-insulating and corrosion-resistant functions. The manufacturing process is simple and the cost is low, and the plate is widely used in multiple technical fields such as construction, automobiles, aerospace, etc.

[0096] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0097] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An inorganic fiber composite aerogel board, characterized in that: Prepared by the following steps: (1) Select a steel plate as the inner panel, and cut the ceramic silicone rubber fiber belt and aerogel felt into the same size; (2) Using the layer laying method, the steel plate, the high temperature resistant flame retardant sealant, the aerogel felt, the high temperature resistant flame retardant sealant, and the ceramicized silicone rubber fiber tape are laid and bonded neatly in sequence; (3) After the laying is completed, it is molded using molding equipment; (4) After the molding is completed, a high temperature resistant flame retardant sealant is applied to the side of the aerogel board for structural edge sealing. After completion, the inorganic fiber composite aerogel board is obtained by allowing it to stand and solidify; The high temperature resistant flame retardant sealant comprises 40-50 parts of terminal hydroxyl polysiloxane, 5-10 parts of cross-linking agent, 10-15 parts of flame retardant, 10-20 parts of nano calcium carbonate, 0.5-2 parts of chain extender, and 0.5-1 parts of stannous octoate; Wherein, the flame retardant is prepared by the following steps: S1. Add 4-aminophenylboronic acid, caged pentaerythritol phosphate and dimethyl sulfoxide into a flask, stir, then add concentrated hydrochloric acid, react at room temperature for 2 h, add sodium carbonate, distill under reduced pressure, wash, and dry to obtain intermediate 1; S2, nitrogen purged the flask, added intermediate 1, 1-piperazine propanol and dimethyl sulfoxide, stirred, added concentrated hydrochloric acid, reacted at room temperature for 3 hours, added sodium carbonate, distilled under reduced pressure, washed, and dried to obtain intermediate 2; S3. Purge the flask with nitrogen, add KH570, mix the intermediate 2 with DMF and add into the flask, react at 60°C for 48h, cool, and distill under reduced pressure to obtain a flame retardant.

2. The inorganic fiber composite aerogel board according to claim 1, characterized in that: The amount ratio of 4-aminophenylboronic acid, caged pentaerythritol phosphate, concentrated hydrochloric acid and dimethyl sulfoxide in step S1 is 7.6g:8.6g:0.025mL:130mL; the amount ratio of intermediate 1, 1-piperazine propanol, concentrated hydrochloric acid and dimethyl sulfoxide in step S2 is 10.5g:5.8g:0.02mL:130mL; the amount ratio of intermediate 2, KH570 and DMF in step S3 is 9.4g:5.5mL:100mL.

3. The inorganic fiber composite aerogel board according to claim 1, characterized in that: The ceramicized silicone rubber fiber belt in step (1) is a composite of one of glass fiber cloth, basalt fiber cloth, and carbon fiber cloth and ceramicized silicone rubber; the aerogel felt is one of glass fiber aerogel felt, basalt fiber aerogel felt, and high silica fiber aerogel felt.

4. The inorganic fiber composite aerogel board according to claim 1, characterized in that: The thickness of the steel plate in step (1) is 1 to 3 mm, the thickness of the ceramic silicone rubber fiber belt is 1 mm, and the thickness of the aerogel felt is 3 to 6 mm; the thickness of the high temperature resistant flame retardant sealant in step (2) is 0.5 to 1 mm.

5. The inorganic fiber composite aerogel board according to claim 1, characterized in that: The molding pressure in step (3) is 3-5 MPa, and the molding holding time is 3 min. The thickness of the high temperature resistant flame retardant sealant in step (4) is 1 mm.

6. The inorganic fiber composite aerogel board according to claim 1, characterized in that: The crosslinking agent is one or more of methyltriacetoxysilane, methyltributylacetonato oxime silane, and methyltrimethoxysilane; the chain extender is one or more of dimethyldibutylketoxime silane, methylvinyldibutylketoxime silane, or methylvinyldiacetoneoxime silane.

7. Application of the inorganic fiber composite aerogel board according to claim 1 in the fields of construction, automobile, and aerospace.

Citation Information

Patent Citations

  • Manufacturing method for ceramic fire-proof cable

    CN103824655A

  • Flame-retardant silicone sealant for building

    CN115851219A